Investigating Indonesian Novice EFL Teachers’ Perceptions On Their Identity Construction - Kristian Florensio Wijaya (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
Previous studies indicated that the majority of second language teachers were in serious hurdles in reconstructing their identities formation. The major hurdles that matter most in this debilitating inhibition are the lack of extensive emotional supports, minimum exposure of teaching ownership, and contradicting educational paradigms. This qualitative study aimed to further investigate Indonesian novice EFL teachers’ perceptions of their identity construction. To gather reliable data, the critical incident technique manifested in the form of seven critical self-reflection inquiries were being asked to 3 invited novice EFL teachers possessing a vast range of teaching experiences resided in various Indonesian educational institutions. Three major themes were drawn from the interviewees’ excerpts namely the importance of inducing more proactive teaching-learning engagement, establishing mutual rapports with learners as well as working colleagues, and rejuvenating the ongoing professional identity construction aligned with external institutional demands.